2020
DOI: 10.29245/2578-2959/2020/2.1203
|View full text |Cite
|
Sign up to set email alerts
|

Economic Strain Deteriorates While Education Fails to Protect Black Older Adults Against Depressive Symptoms, Pain, Self-rated Health, Chronic Disease, and Sick Days

Abstract: Background: A large body of empirical evidence on Minorities' Diminished Returns (MDRs) suggests that educational attainment shows smaller health effects for Blacks compared to Whites. At the same time, economic strain may operate as a risk factor for a wide range of undesired mental and physical health outcomes in Black communities. Aim:The current study investigated the combined effects of education and economic strain on the following five health outcomes in Black older adults in underserved areas of South … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 179 publications
1
4
0
Order By: Relevance
“…A larger sample size might show the effect of education and income in our study. However, our previous similar analysis in a larger sample showed similar findings [ 41 ]. Third, our study was cross-sectional.…”
Section: Discussionsupporting
confidence: 80%
See 3 more Smart Citations
“…A larger sample size might show the effect of education and income in our study. However, our previous similar analysis in a larger sample showed similar findings [ 41 ]. Third, our study was cross-sectional.…”
Section: Discussionsupporting
confidence: 80%
“…In one study in South Los Angeles [ 117 ], financial strain predicted chronic disease, chronic pain, self-rated health, depression, and the usage of sick days. In another study, financial strain was a risk factor for poor self-rated health, chronic pain, sick days, chronic disease, and depression, while education failed to show any protective effect for the same community [ 41 ]. Similar to the current study, that study compared the role of financial strain with education and showed similar results [ 41 ].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Depressive symptoms are associated with multiple indicators of poor mental and physical health, including major depressive disorder (Moazen-Zadeh & Assari, 2016), cardiovascular diseases (Xiang & An, 2015), declines in cognitive function (Turner et al, 2015), and specific- and all-cause mortality (Assari et al, 2016; Liwo et al, 2020). Middle-aged and older adults may be at an increased risk of experiencing depressive symptoms due to unexpected changes in employment (Abrams et al, 2021), financial strain (Assari et al, 2020), increased frailty (Mezuk et al, 2012), greater feelings of loneliness (Taylor & Nguyen, 2020), and increases in disability, sleep disturbances, and bereavement (Cole & Dendukuri, 2003). Older Black Americans experience relatively similar age-related risk factors for depressive symptoms as whites (Pickett et al, 2013) but are at an even greater risk for poor mental health due to their experiences of racism, discrimination, and socioeconomic disadvantage (Williams & Williams-Morris, 2000).…”
Section: Introductionmentioning
confidence: 99%